Study of Macro- and Mesodamage of Remolded Loess under Alternating Dry and Wet Conditions in an Acid Rain Environment - Wanjun Ye; Yuntao Wu; Yang Bai (Advances in Materials Science and Engineering)
As a national development plan, ecological protection of the Yellow River Basin has attracted extensive social attention in recent years. Considering the influence of acid rain on the engineering characteristics of loess in this area, we investigated changes in the physical and mechanical characteristics of remolded loess under the combined action of acid rain and dry-wet cycles by means of triaxial tests, nuclear magnetic resonance spectroscopy, and scanning electron microscopy. The results are as follows: in the acidic environment, the stress-strain relationship of remolded loess undergoes stress hardening after dry-wet cycling. The cohesion and internal friction angle of remolded loess are negatively correlated with the number of cycles. From the multiscale analysis of the dry-wet cycle process under acid rain condition, the T2 spectrum of the test soil has three peaks at the micropore level. With the increasing number of cycles, the spectral area increases gradually, and the sample transitions from small pores to large- and medium-size pores. At the microscopic level, the clay mineral particles among soil particles decrease in size, the contact mode between soil particles develops from stable to unstable, the particles are gradually rounded, and the fractal dimension decreases. Chemical erosion and physical erosion are special features of this experiment. Physical erosion causes particle erosion and pore growth, while chemical erosion includes reactions by feldspar. Together, physical and chemical reactions aggravate the soil deterioration process. These research results have laid a good experimental foundation for the ecological protection of the Yellow River Basin.